Classification of some blended spectral lines of praseodymium. (13th May 2015) - Uddin, Zaheer; Siddiqui, Imran; Tanweer, Jaweria; Jilani, Saif Uddin; Windholz, Laurentius
Abstract: Praseodymium has a huge number of fine structure levels and correspondingly a high density of spectral lines. Thus in highly resolved Fourier transform spectrum blend situations or convolutions of two or more spectral lines, having nearly the same center of gravity wave number, are frequently observed. Such lines arise from the combination of different pairs of fine structure levels with similar energy differences. The hyperfine structure patterns of these lines overlap, and sometimes individual hyperfine components are either not visible or are difficult to identify. In this work we present some blends of two lines in which one of the lines is still unclassified. We are able to resolve these blend situations and to find the missing levels. Altogether, 11 new levels are presented in this paper. Five of them belong to odd parity configurations and six belong to even configurations. The new levels classify 49 spectral lines.